Transformasi Sakralitas dan Intimitas di Era Digital: Menimbang Pernikahan Virtual dalam Perspektif Sosio-Yuridis: The Transformation of Sacrality and Intimacy in the Digital Era: Understanding Virtual Weddings from a Socio-Legal Perspective - Ita Ma’rifatul Fauziyah; Nikmatul Azizah (Besari: Journal of Social and Cultural Studies, 2025)
The digital age has fostered the emergence of virtual marriage, posing unprecedented legal and socio-cultural challenges. This study examines the socio-cultural implications of digital marriage and analyzes the transformation of ritual meaning in the era of mediatization. Utilizing a qualitative approach with thematic analysis and case studies from various Indonesian regions, this research evaluates how technology redefines the concepts of "sacredness" and "presence" through the lens of Randall Collins' interaction ritual chains and Erving Goffman's dramaturgy. Findings reveal that while technology offers accessibility and efficiency, it also triggers the deinstitutionalization of marriage, where traditional rites of passage are transformed into mediatized projects oriented toward social visibility and the "experience economy." The study concludes that the success of virtual rituals depends on the ability of participants to synchronize their focus and emotional energy despite physical distance. Recommendations include the development of a flexible socio-legal framework that acknowledges digital intimacy while preserving the fundamental essence of the marriage institution as a communal pillar. Era digital memicu fenomena pernikahan virtual yang menghadirkan tantangan hukum dan sosial-budaya baru. Penelitian ini bertujuan mengkaji implikasi sosial-budaya pernikahan digital dan menganalisis transformasi makna ritual dalam era mediatisasi. Menggunakan pendekatan kualitatif dengan analisis tematik dan studi kasus dari berbagai wilayah di Indonesia, studi ini mengevaluasi bagaimana teknologi mendefinisikan ulang konsep "kesakralan" dan "kehadiran" melalui lensa teori rantai ritual interaksi Randall Collins dan dramaturgi Erving Goffman. Hasil penelitian menunjukkan bahwa meskipun teknologi menawarkan aksesibilitas dan efisiensi, ia juga memicu deinstitusionalisasi pernikahan, di mana ritus peralihan tradisional berubah menjadi proyek mediatisasi yang berorientasi pada visibilitas sosial dan "ekonomi pengalaman." Studi ini menyimpulkan bahwa keberhasilan ritual virtual bergantung pada kemampuan partisipan untuk menyinkronkan fokus dan energi emosional meskipun terpisah secara fisik. Rekomendasi yang diajukan meliputi pengembangan kerangka sosial-hukum yang fleksibel yang mengakui intimitas digital sambil tetap mempertahankan esensi fundamental institusi pernikahan sebagai pilar komunitas.